Nonlinear boundary-layer problems and laminar vortical stream generated by resonant sloshing in a circular-base tank - Timokha, A.N. (Нелінійні коливання, 2018)
For a viscous incompressible liquid with laminar flows, nonlinear boundary-layer problems on the wetted
tank surface (wall and bottom) of a rigid circular-base tank partly filled with a finite depth are derived assuming known the resonant steady-state inviscid liquid sloshing due to a horizontal translatory
orbital tank motion with the forcing frequency close to the lowest natural sloshing frequency. By adopting a Narimanov – Moiseev-type approximation of the above-mentioned inviscid sloshing, an analytical
asymptotic solution of the derived boundary-layer problems is constructed to prove that the inviscid flows
must contain a global stationary vortex component. A new nonlinear boundary-value problem governing
this component is derived. За припущення в’язкої нестисливої рiдини з ламiнарною течiєю виведено нелiнiйнi крайовi задачi пришарових течiй бiля змоченої поверхнi бака (стiнки та дна) вертикального кругового
цилiндричного бака, який частково заповнений рiдиною iз скiнченною глибиною. Допускаючи,
що вiдомо резонанснi усталенi нев’язкi течiї рiдини (хлюпання), якi збурюються горизонтальними поступальними орбiтальними рухами бака iз частотою, яка є близькою до першої власної
частоти коливання рiдини, та використовуючи наближення Нарiманова – Моiсеєва вищезазначених усталених нев’язких режимiв хлюпання, ми будуємо асимптотичний аналiтичний розв’язок виведених задач пришарової течiї. Доведено, що цi нев’язкi хлюпання повиннi мiстити глобальну стацiонарну вихрову компоненту. Виведено нову нелiнiйну крайову задачу, розв’язок якої
описує цю компоненту.